MANF brakes TLR4 signaling by competitively binding S100A8 with S100A9 to regulate macrophage phenotypes in hepatic fibrosis - Chao Hou; Dong Wang; Mingxia Zhao; Petek Ballar; Xinru Zhang; Qiong Mei; Wei Wang; Xiang Li; Qiang Sheng; Jun Liu; Chuansheng Wei; Yujun Shen; et al. (Elsevier, 2023)
The mesencephalic astrocyte-derived neurotrophic factor (MANF) has been recently identified as a neurotrophic factor, but its role in hepatic fibrosis is unknown. Here, we found that MANF was upregulated in the fibrotic liver tissues of the patients with chronic liver diseases and of mice treated with CCl4. MANF deficiency in either hepatocytes or hepatic mono-macrophages, particularly in hepatic mono-macrophages, clearly exacerbated hepatic fibrosis. Myeloid-specific MANF knockout increased the population of hepatic Ly6Chigh macrophages and promoted HSCs activation. Furthermore, MANF-sufficient macrophages (from WT mice) transfusion ameliorated CCl4-induced hepatic fibrosis in myeloid cells-specific MANF knockout (MKO) mice. Mechanistically, MANF interacted with S100A8 to competitively block S100A8/A9 heterodimer formation and inhibited S100A8/A9-mediated TLR4-NF-κB signal activation. Pharmacologically, systemic administration of recombinant human MANF significantly alleviated CCl4-induced hepatic fibrosis in both WT and hepatocytes-specific MANF knockout (HKO) mice. This study reveals a mechanism by which MANF targets S100A8/A9-TLR4 as a "brake" on the upstream of NF-κB pathway, which exerts an impact on macrophage differentiation and shed light on hepatic fibrosis treatment.